Influencia de proteína aislada del suero de leche y mezclas de dos estabilizantes en la elaboración de un helado artesanal - Loor Reyes, Abrahan Calixto (2019)
In this work, the use of whey protein isolate and mixtures of two gums as stabilizers in the production of artisanal ice cream was evaluated. Two levels of whey protein isolate (3 and 5%) and gum mixtures (0.3 and 0.5%) were applied; which resulted in four treatments, the research was conducted with a completely randomized design and three replicas. The experimental unit consisted of 15 kg of ice cream paste. The response variables were: percentage of total proteins, viscosity, syneresis and weight-volume range. Regarding the variable protein content, the treatments applied showed higher percentages in the analyzes performed; Similarly, high values in viscosity and weight-volume ratio were evidenced in comparison to the NTE INEN 706 (2005) standards and in comparison to other investigations taken as references. It is highlighted that there was absence of syneresis in all treatments. The results obtained of total solids were high in relation to the minimum requirement of the NTE INEN 706 (2005) standard for ice cream; similarly, a high percentage of total proteins could be evidenced in a range of 3.21 to 4.74% in reference to said norm. It is concluded that the characteristic of the ice cream was expected due to the considerable fat content and the high contribution of total solids.